THE INFLUENCE OF PROMOTIONS AND DISTRIBUTION CHANNELS ON THE SALES VOLUME OF SURVEY PRODUCTS AT MSME CENTERS IN SORONG CITY - Sismar, Andi; Mahfudnurnajamuddin, Mahfudnurnajamuddin; Serang, Serlin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The advancement of a company or business is an exceptional achievement for any company or business. Selecting the right promotion and diversifying products during critical stages in the product cycle are crucial in deciding the future success or closure of a business. There's no escaping the fact that the sales level serves as a pivotal indicator of whether a company can thrive in the business world. This research adopts a quantitative approach, with 100 SME perpetrators and owners in the Sorong district as respondents. The hypothesis posits that there is a correlation between promotion strategies, distribution channels, and sales volume. The test results support the alternative hypothesis (Ha) over the null hypothesis (Ho), indicating a significant influence of promotion and distribution channels on sales volume. Based on the regression equation Y = 17.049 + 0.511X1 + 0.356X2, it can be inferred that each unit increase in promotion and distribution levels leads to a respective increase in sales volume, keeping other factors constant. Hypothesis testing using F statistics revealed a significant Fcount of 70.728 compared to the critical Ftable value. This confirms the acceptance of Ha and the rejection of Ho. These findings imply that an increase in sales volume is positively impacted by effective promotion and distribution strategies, contributing to the overall health of SMEs.